Perubahan Sosial Masyarakat di Jazirah Arab: Transformasi Kultural Ashabiyah dalam Menunjang Kekuasaan Nabi Muhammad - Muhamad Yusrul Hana (Institut Agama Islam Negeri Kendari, 2020)
Ashabiyah has become one of the important social systems for people in the Arabian Peninsula before the Prophet Muhammad introducing Islam to Mecca. Ashabiyah brought the tribes into one strong unity in Arab, though it turned out this system often leads to egoism and aggression of each group, which caused dispute and war. The Prophet Muhammad then used this system to unify the people of the desert and the people within the country once again with a new purpose, which is Islam, after Islam came into Arabic. The primary purpose of the ashabiyah system was unification and sovereignty for all the people, and it costs the system to have a guideline of religious values. So, based on the values every act made by the tribe will lead to right action as well. This research wants to explain how did Ashabiyah take a role in all peoples of Arabia and be a succession of Prophet Muhammad (PBUH) in the spread of Islam. The method that is used in this study is that historical research contains heuristic, criticism, interpretation, and historiography. The results of the study showed that the ashabiyah based on Islam became a strong system in building the progress of the ummah because, without social solidarity, unity, and help, the ideals of sovereignty could not be realized.